Hospital Pharmacy: Comprehensive management of medical devices during SARS-CoV-2 - Seira Climent-Ballester; Juan Selva-Otaolaurruchi (Farmacia Hospitalaria)
Medical devices have become essential to the prevention and control of the COVID-19 pandemic, being crucial for health professionals and patients in particular, and the population in general. It is important to be aware of the laws that regulate the management, distribution, and control of medical devices. Article 82 of the Spanish Law 29/2006 on Guarantees and Rational Use of Medicines and Medical Devices establishes that it is the responsibility of Hospital Pharmacy Services “to participate in and coordinate the purchase of medicines and medical devices in the hospital to ensure an efficient acquisition and rational use of medical devices”. For this reason, working groups of the Spanish Society of Hospital Pharmacy and other scientific societies have issued technical guidelines and consensus statements to provide technical support and updated information on the use of masks, individual protection equipments and other medical devices. In addition, the shortage of medical devices caused by the high demand has resulted in the uncontrolled production and distribution of medical devices. This phenomenon, added to the fraudulent selling of medical devices, highlights the need for a closer surveillance of the market to guarantee the efficacy and safety of available medical devices. A rational use of medical devices is necessary to ensure the availability and safety of these products, which requires the involvement of different stakeholders, including hospital pharmacists. Thus, it is essential that hospital pharmacists receive specific training in technical aspects concerning the possession and use of medical devices. This will help guarantee an effective and safe use of medical products. The acquisition and use of medical devices requires a keen understanding of the technical and legal aspects concerning these products, which makes hospital pharmacists essential for the integral management of medical devices.